Effectiveness Of Art Therapy To Reduce Social Anxiety Of Bullying Victims Reviewed From Gender - hakim, lukman (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2019)
Those who are victims of bullying are more at risk of experiencing various health problems, both physically and mentally, including low psychological well-being and experiencing social anxiety characterized by reduced self-confidence, antisocial, fear of meeting the perpetrators, social adjustment becomes worse.This study aims to test Art therapy whether it is effective for reducing social impairment of victims of bullying, differences in social anxiety between men and women, differences in anxiety between men and women after being given Art therapy. This research was conducted on the subject of SMP Bina Bangsa students, with an experimental research method, using the one grouppretest-posttest design. Data analysis used the SPSS Mann Whitney test, Independent Sample T-Test and qualitative analysis.This research has proven the significant results that Art therapy can influence to reduce the level of social anxiety of Bullying victims, with a P value: 0.006 smaller than 0.05. There is a difference in anxiety between men and women with a sig. value 0.003 smaller than 0.05. There was no difference in social anxiety between men and women after getting Art therapy with a P value = 0.772 greater 0.05.Â Copyright Â© 2019. Pusat Penelitian dan Layanan Psikologi.